(untitled) (Community Based Medical Journal, 2014)
Hypertension is the most common medical problem encountered in pregnancy and are leading causes of maternal, fetal and neonatal morbidity and mortality worldwide. Definitions, classifications, assessment and management of hypertensive disorders vary considerably in the literature and from country to country. In light of this, we aimed to evaluate different types of hypertensive disorders of pregnancy and to determine the impact of hypertensive disorders of pregnancy (HDP) on maternal, fetal and neonatal outcomes. This Cross Sectional descriptive study was conducted in the Department of Gynaecology and Obstetrics of Community Based Medical College, Mymensingh, Bangladesh from April 2012 to March 2013. All the patients who were diagnosed with HDP and gestational age of 20-40 weeks during the study period were included in the study. Patients with preexisting renal disease, diabetes mellitus, active urinary tract infection or who refused to cooperate with the study were excluded. The data regarding demographic variables, clinical features, pregnancy characteristics, maternal complications, fetal and neonatal outcomes were gathered from available data on medical record files. Edema was the most common clinical symptom. Primipara mothers were predominant in the both mild and severe preeclampsia group. Majority (88%) of mothers in mild preeclampsia group had a history of spontaneous vaginal birth, however 82.9% in severe preeclampsia group by Lower Segment Caesarean Section (LSCS). A higher proportion of mother in mild preeclampsia group delivered at term, whereas 65.7% in severe preeclampsia group delivered preterm. The proportion of maternal complications such as were significantly higher in severe preeclampsia group than those in mild preeclampsia group. Most babies (92%) were born with a birth weight 2500 grams in mild preeclampsia group, while 70% born with birth weight between 1500 - 2499 grams in severe preeclampsia group. All the babies were born with apgar score less than 7 between mild and severe preeclampsia groups. About three quarter (74.3%) of neonates born to women the severe preeclampsia group required resuscitation compared to 40% in mild preeclampsia group. The maternal death, still birth and neonatal death were found higher in severe preeclampsia group than those in mild preeclampsia group. Pregnancies affected by hypertensive disorders require careful monitoring due to the increased risks of adverse pregnancy outcomes. Frequency of severe hypertensive disorders is high in our set up. It is associated with high maternal, fetal and neonatal mortality CBMJ 2014 January: Vol. 03 No. 01 P: 46-52